Influence of the Geometric Parameters on the Densification Onset Strain of Double-Walled Honeycomb Aluminum under Out-of-Plane Compression - Jian Wang; Ying Cao (Advances in Materials Science and Engineering)
As a material widely used in various lightweight structures and energy absorbing devices, honeycomb aluminum has high specific stiffness and specific strength, excellent energy absorption capacity, and vibration damping. When evaluating the energy absorption of honeycomb aluminum under out-of-plane compression, platform stress and onset strain of densification have become important parameters studied by many scholars. In this work, based on the theory that the energy absorption efficiency determines the densification onset strain, the influence of the geometric design parameters of honeycomb aluminum on the onset strain of out-of-plane quasi-static compression densification is studied. Based on the results of the finite element analysis, the relationship between the onset strain and the geometric design parameters including cell size length and wall thickness is fitted by the least squares method. A linear relationship that the onset strain of densification will decrease with the increase of the reciprocal of cell side length and the onset strain of densification will decrease with the increase of the wall thickness is exhibited in the conclusion. This work can provide a theoretical basis for the calculation of the platform stress in the plastic deformation stage.